The moderating effect of perceived organizational support in the relationship between emotional labour and job attitudes: A study among health professionals - Joshua King Safo Lartey; Kwesi Amponsah‐Tawiah; Joseph Osafo (Wiley, 2019)
Abstract Aim The present study was set out to establish the link between emotional labour (surface and deep acting) and job attitudes (job satisfaction organizational commitment) by introducing perceived organizational support as a moderating variable. Design The study made use of a cross‐sectional design by sampling three hundred and forty‐two (342) nurses and midwives from six health facilities in Ghana. Methods The study employed a quantitative approach to examine the relationships between the study variables. Results The study disclosed that whereas surface acting related negatively with job satisfaction but not with organizational commitment, deep acting did not relate significantly with both job satisfaction and organizational commitment. Perceived organizational support as a moderating variable showed a significant moderating effect between surface acting and job attitudes. However, Perceived organizational support moderated the relationship between deep acting and organizational commitment but not job satisfaction. The findings pose much contextual relevance to health professionals where emotional regulations are core responsibilities of health care.